Splenomegaly, Cardiomegaly, and Osteoporosis in a Child with Gaucher Disease - J. J. Sheth; C. M. Ankleshwaria; M. A. Mistri; N. Nanavaty; S. J. Mehta (Hindawi Limited, 2011)
A 15-month-old girl, born to the consanguineous parents, was referred with the sign of massive splenomegaly associated with thrombocytopenia and anemia. Plasma Chitotriosidase estimation was carried out as a screening test and was found to be normal with reduced activity of β-glucosidase in leucocytes suggestive of Gaucher disease. At the age of 4 years, severe osteoporosis and cardiomegaly with pulmonary congestion were observed in the child. Molecular analysis for GBA gene has revealed homozygous status for L444P (c.1448C) in the proband, whereas parents and two elder sisters were found to be heterozygote. Prenatal study during the fourth pregnancy was carried out from cultured chorionic villi for β-glucosidase, which was in the carrier range. Further confirmation of the carrier status was carried out from amniotic fluid DNA and was found to be heterozygous for L444P (c.1448C) in the GBA gene. This case demonstrates that children with the sign of splenomegaly with anemia and thrombocytopenia need to be screened for Gaucher disease, and molecular study can further help to confirm the heterozygous status, where prenatal study by enzyme investigation demonstrate heterozygous condition.